2005
DOI: 10.1016/j.jhsb.2004.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Full Thickness Skin Graft for Nail Unit Reconstruction

Abstract: A retrospective study of 13 patients assessed the use of a full thickness skin graft for nail unit reconstruction after total nail unit removal for nail bed malignancies. No failures of the graft were observed and no patient had recurrence of the malignant tumour at 4 year follow-up. Full thickness skin grafting is a simple procedure which provides a good cosmetic outcome and does not produce significant donor site morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
84
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(93 citation statements)
references
References 15 publications
9
84
0
Order By: Relevance
“…4 Recently, however, some authors have suggested a non-amputative conservative treatment of subungual melanoma to preserve the phalangeal bone for in situ or thin lesions of subungual melanoma. 5,6,[18][19][20] Few publications provide Abbreviations: A&W, alive and well; NA, not available.…”
Section: Discussionmentioning
confidence: 99%
“…4 Recently, however, some authors have suggested a non-amputative conservative treatment of subungual melanoma to preserve the phalangeal bone for in situ or thin lesions of subungual melanoma. 5,6,[18][19][20] Few publications provide Abbreviations: A&W, alive and well; NA, not available.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting defect can be repaired either with a split-or full-thickness skin graft. [48][49][50][51][52] Although it is possible to allow wound healing by secondary intention, this will often result in a surface that is not smooth and can have spicules of keratinizing tissue and, thus, is not as comfortable for the patient as the results obtained with a skin graft.…”
Section: Melanoma In Situmentioning
confidence: 99%
“…He also had pain and swelling of the soft tissues of the finger tips. Like the treatment of subungual soft tissue sarcomas reported by Lazar et al [3] we chose to treat the finger lesion by a complete resection of the nail unit (R0) to avoid amputation [5]. Lazar et al based their strategy on anatomical considerations and analysis of other reports.…”
Section: Discussionmentioning
confidence: 99%
“…We did an en bloc resection of the nail unit [3] for the thumb lesion (Figure 1a) with immediate coverage using a full thickness skin graft. The ring finger was not reoperated on.…”
Section: Case Reportmentioning
confidence: 99%